2016
DOI: 10.4088/jcp.15m09938
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Synthetic Cannabinoid and Cannabis Users Admitted to a Psychiatric Hospital

Abstract: Patients admitted following use of SC are generally younger males who have higher severity of psychotic symptoms at admission, are more likely to be admitted by criminal court order, and require longer hospitalization periods in comparison to cannabis users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The full text of remaining 216 papers was searched, and a further 192 papers excluded due to not fulfilling the inclusion criteria (Fig 1). After abstraction and full text screening, a total of 24 articles were selected for review: 2 toxicology reports (Monte et al, 2017;Waugh et al, 2016), 4 casecontrol studies (Altintas et al, 2016;Bassir Nia et al, 2016;Shalit et al, 2016;Welter et al, 2017), 3 cross-sectional analyses (Glue et al, 2013;Manseau et al, 2017;Vallersnes et al, 2016) and 15 case reports (Barcelo et al, 2017;Benford and Caplan, 2011;Coppola and Mondola, 2017;Hurst et al, 2011;Johnson et al, 2011;Mahgoub and Young, 2017;Meijer et al, 2014;Muller et al, 2017;Oliveira et al, 2017;Oluwabusi et al, 2012;Ozer et al, 2016;Roberto et al, 2016;Rojek et al, 2017;Samaan et al, 2016; Van der Veer and Friday, 2011) ( Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The full text of remaining 216 papers was searched, and a further 192 papers excluded due to not fulfilling the inclusion criteria (Fig 1). After abstraction and full text screening, a total of 24 articles were selected for review: 2 toxicology reports (Monte et al, 2017;Waugh et al, 2016), 4 casecontrol studies (Altintas et al, 2016;Bassir Nia et al, 2016;Shalit et al, 2016;Welter et al, 2017), 3 cross-sectional analyses (Glue et al, 2013;Manseau et al, 2017;Vallersnes et al, 2016) and 15 case reports (Barcelo et al, 2017;Benford and Caplan, 2011;Coppola and Mondola, 2017;Hurst et al, 2011;Johnson et al, 2011;Mahgoub and Young, 2017;Meijer et al, 2014;Muller et al, 2017;Oliveira et al, 2017;Oluwabusi et al, 2012;Ozer et al, 2016;Roberto et al, 2016;Rojek et al, 2017;Samaan et al, 2016; Van der Veer and Friday, 2011) ( Figure 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Shalit and colleagues studied patients admitted to a psychiatric ward in Israel who reported SCRA use and compared them to patients admitted who reported NC but not SCRA use (Shalit et al, 2016). The SCRA users were younger than NC users, had longer admissions, and more marked psychotic symptoms (PANSS total score of 82.5 vs. 70).…”
Section: Case-control Studiesmentioning
confidence: 99%
“…In contrast to D9-Tetrahydrocannabinol (D9-THC) which is the main psychoactive constituent of cannabis, SCs are more potent and efficacious at cannabinoid CB 1 and CB 2 receptors (Pertwee, 2008;Bhattacharyya et al, 2012;Castaneto et al, 2014). Therefore, although SC drugs are designed to mimic the effects of cannabis, they induce more severe and persistent adverse effects since they include more potent and toxic psychoactive compounds than traditional cannabis (Fattore, 2016;Cohen et al, 2017;Cohen & Weinstein, 2018a,b;Langer et al, 2014;Shalit et al, 2016;van Amsterdam et al, 2015;Weinstein et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In psychiatric patients, the comparison of natural cannabis users with synthetic cannabinoid users has revealed that the synthetic-cannabinoid-using group demonstrates more severe psychotic symptoms and agitation [7,8]. It is known that long-term natural cannabinoid use increases the risk of development of mental disorders such as anxiety, depression, bipolar disorder and schizophrenia [9][10][11].…”
Section: Resultsmentioning
confidence: 99%